PENGEMBANGAN MEDIA PEMASARAN BERBASIS POTENSI LOKAL DANAU TEMPE MELALUI INTERNET MARKETING UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT KABUPATEN WAJO - Eriyana, Elvis; Husain Syam; Jamaluddin (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2024)
This study aims to find out the type of local potential dried fish marketing media of Lake Tempe that is valid, practical to use and effective in improving the welfare of the people of Wajo Regency. This research uses research and development (Research and Development) with the 4 D's type. The data collection instruments were selected observation, interview, questionnaire and documentation techniques. The population and research sample are 40 samples from two villages, namely Assorajang Village and Pakkanna Village. The data analysis technique used in this study is to calculate the valid and practical scale of the product. Test the validity level of packaging by 87% and the validity of web marketing by 85%. The test of the practicality level of packaging is 88% with the category of very practical while the test of the level of practicality of web marketing is 84% with the category of very practical. The results of this study state that the marketing and packaging web is feasible to increase the selling price of potential products of Lake Tempe so that if carried out sustainably, it can improve the welfare of potential business actors of Lake Tempe.